1992
DOI: 10.1002/hipo.450020303
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of cerebral hypoxic‐ischemic damage

Abstract: The four most prominent hypotheses on the cellular processes leading to hypoxic-ischemic neuronal damage or death are (1) the lactacidosis hypothesis, (2) the calcium overload hypothesis, (3) the excitotoxic hypothesis, and (4) the oxygen-free radical hypothesis. The authors comment on the evidence in favor of and against each in an attempt to select the one hypothesis that best explains the mechanism of cerebral hypoxic-ischemic damage while withstanding the scrutiny of scientific testing. A major part of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…It has been demonstrated that during ischemic states, brain production of free radicals such as superoxide causes increased re lease of excitatory amino acids which are endowed with neurotoxic effects (Pellegrini-Giampietro et ai., 1990). Also, the free radical hypothesis in hyp oxic-ischemic cell injury shares a common path with the excitotoxic hypothesis, i.e., its depen dence on calcium (Orrenius et ai., 1989), and it has been proposed that free radicals, either alone or in combination with excitatory amino acids, may en hance calcium influx and overload to exacerbate neuronal damage (Halliwell, 1992;Schurr and Rigor, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that during ischemic states, brain production of free radicals such as superoxide causes increased re lease of excitatory amino acids which are endowed with neurotoxic effects (Pellegrini-Giampietro et ai., 1990). Also, the free radical hypothesis in hyp oxic-ischemic cell injury shares a common path with the excitotoxic hypothesis, i.e., its depen dence on calcium (Orrenius et ai., 1989), and it has been proposed that free radicals, either alone or in combination with excitatory amino acids, may en hance calcium influx and overload to exacerbate neuronal damage (Halliwell, 1992;Schurr and Rigor, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…As this field has matured, a host of potential mediators of ischemic injury has been described: EAAs, free cytosolic Ca*+, acidosis, oxygen radicals, and so on. As a source of considerable tautological confusion, each of these putative mediators of injury can potentially interact with and exacerbate the toxicity of others (Siesjo, 1988b;Schurr and Rigor, 1992). These interactions emphasize the importance of defining a temporal sequence of the various biochemical derangements induced by ischemia, a task made more difficult by the heterogeneity of experimental systems used to model the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of selective neuronu1 vulnerability, though, the relationship between acidosis and ischemic cell injury is less obvious. However convincing the acidotic hypothesis may have been, recent work has cast doubt about its primacy, emphasizing that acidosis is only part of a complex and dynamic series of events in the ischemic brain (Schurr and Rigor, 1992). …”
mentioning
confidence: 99%
“…Some investigators have reported reduced neuronal injury from oxygen deprivation using glutamate antagonists in dissociated cell cultures (Goldberg et al, 1987;Marcoux et al, 1990) or in acutely prepared hippocampal slices (Clark and Rothman, 1987). Other investigators have reported that glutamate receptor antagonists do not effectively reduce neuronal damage following oxygen deprivation alone (Aitken et al, 1988;Lipton and Lobner, 1990;Schurr and Rigor 1992;Friedman and Haddad, 1993;Haddad and Jiang, 1993). These previous studies raise the possibility that the nature and severity of the insult.…”
mentioning
confidence: 80%